Expert’s Perceptions towards Management of Tourist Traffic in Protected Areas Based on the Tatra Mountains - DELEKTA, Anna; FIDELUS-ORZECHOWSKA, Joanna; CHROBAK, Anna (Journal of Environmental Management and Tourism, 2020)
Increasing human impact in mountain areas may constitute a challenge to national park authorities. Therefore, interdisciplinary research is important in order to address the various aspects of the functioning of protected areas. The purpose of the present study was to analyze perceptions of infrastructure and tourist traffic in the Tatra Mountains by tourist experts. Data were collected using the diagnostic survey method and in-depth interviews with experts. Statistical analysis included the use of the U-Mann-Whitney Test and the nonparametric Chi Square Test. Research has shown differences in the way both local transportation and restaurant services are viewed in the Polish and Slovakian parts of Tatras. Experts indicate that the main reason for increasing tourist traffic is that the Tatras are in fashion, while the key problem is excess litter generation.